Incarnation and Icon in the Polemical Works of St. John of Damascus - Kerezova, Alena (Forum Theologicum Sardicense, 2025)
Alena Kerezova (Doctoral student at the Sofia Univeristy), Incarnation and Icon in the Polemical Works of St. John of Damascus. The proposed text aims to present the meaning of the dogma of the Incarnation in relation to the representation of God, as articulated in the polemical writings of St. John Damascene, one of the most significant defenders of icon veneration. The Trinitarian and Christological dogmas, along with the role of the Incarnation as a foundational creed for the existence of holy icons, are briefly outlined. John Damascene places particular emphasis on the methods of exposition, highlighting the role of the icon in the life of the Church. The primary work referenced is his “Three Apologetic Treatises Against the Insulting Holy Images,” which responds to the contemporary iconoclastic controversies of his time. Special attention is given to the fact that for the faithful, the icon and its veneration serve as a living proclamation of the saving mystery of the Incarnation of God.